2020
DOI: 10.21203/rs.3.rs-27400/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrupted Rhythms of Life, Work and Entertainment Behaviours and Their Associations with Mental Health Problems under the Stress of COVID-19 Epidemic: A Survey in 5854 Chinese People with Different Backgrounds

Abstract: BACKGROUND and OBJECTIVE The rhythms of life, work and entertainment behaviours are considered as the external behavioural manifestations of biological rhythm.To evaluate the distinctive disrupted rhythms of behaviours and their associations with mental health problems in people with different backgrounds under the stress of COVID-19 epidemic.SUBJECTS AND METHODS A cross-sectional study was conducted from 10-17 March 2020 under the stress of COVID-19 epidemic.A structured e-questionnaire containing general inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…All studies were conducted between January 2020 and September 2020: eight in January, 36 in February, 13 in March, 13 in April, six in May, two in June, two in July and one in September. Twenty preprint studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] were included in the analyses. All studies included in this meta-analysis were of cross sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were conducted between January 2020 and September 2020: eight in January, 36 in February, 13 in March, 13 in April, six in May, two in June, two in July and one in September. Twenty preprint studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ] were included in the analyses. All studies included in this meta-analysis were of cross sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…The overall pooled point estimates of prevalence for anxiety varied between 8% and 91%, which was reported by 73 studies [ [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [28] , [29] , [30] , 32 , 34 , 35 , [37] , [38] , [39] , [42] , [43] , [44] , [45] , [46] , 48 , 49 , 51 , [53] , [54] , [55] , [56] , [57] , 62 , [64] , [65] , [66] , [67] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] ,…”
Section: Resultsmentioning
confidence: 99%
“…The Covid-19 pandemic has also shown that women experience more psychological distress than men and have higher levels of anxiety and depression [32][33][34][35]. As a result, due to the uncertainty of the Covid-19 pandemic, women in this period saw their menopausal symptoms as a threat to their health and that it increased their stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…Later, new behaviors start to emerge. Some of these habits bring about a change in the rhythm of daily activities,[ 1 ] while the mental health of both women and men was damaged. [ 2 3 ] This also includes school children and university students who have been framed by school and university rhythms before the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%